Analisis Keselamatan Pada Perlintasan Sebidang JPL 118 Jalan Raya Lemah Abang Bekasi - Firdaus, Muhammad Fa’iq; Yuniarti, Sri; Widayatie, Sri (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2025)
Level crossings between railway tracks and highways are critical points in the transportation system that require serious attention to safety aspects. One location of concern is the JPL 118 Level Crossing on Lemah Abang Highway, Bekasi Regency. In the last three years (2022–2024), there have been three accidents at this location resulting in fatalities. This study aims to evaluate safety at the crossing through analysis of traffic volume, road infrastructure, road geometric conditions, and road user behavior. The data or information used consists of secondary data obtained from the Directorate General of Railways and primary data obtained from direct field surveys. Data processing methods include calculating the average daily traffic volume to determine the average daily traffic volume, using the basic capacity formula to calculate road capacity, using the V/C Ratio formula to calculate the service level, using the Railway Passenger Car Unit (SMPK) formula, analyzing road facility completeness, analyzing road geometry, and conducting risk analysis using the HIRARC approach. The research results indicate that the service level is at D or unstable flow, with an SMPK value of 382,044 SMPK. Some safety elements do not meet technical standards, safety facilities are incomplete, and there is a high level of road user behavior violations.